2003
DOI: 10.1103/physrevlett.90.233006
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Ultrafast Dissociation Probed by the Doppler Effect in Resonant Photoemission fromCF4

Abstract: The resonant Auger spectrum from the decay of F 1s-excited CF4 is measured. Several lines exhibit a nondispersive kinetic energy as the exciting photon energy is tuned through the resonance region. The F 1s(-1) atomiclike Auger line is split into two components due to the emission of Auger electrons by a fragment in motion, when electron emission is observed along the polarization vector of the light. This Doppler splitting is direct evidence that the core excitation leads to T(d)-->C(3v) symmetry lowering, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
(29 reference statements)
4
27
1
Order By: Relevance
“…The Doppler effect in electron emission has been previously observed in the special case of ultrafast fragmentation following core excitation in isolated molecules [23][24][25] . However, the origin of such Doppler splitting is different from the present case, since it originates from the kinetic energy released by ultrafast dissociation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The Doppler effect in electron emission has been previously observed in the special case of ultrafast fragmentation following core excitation in isolated molecules [23][24][25] . However, the origin of such Doppler splitting is different from the present case, since it originates from the kinetic energy released by ultrafast dissociation.…”
Section: Resultsmentioning
confidence: 95%
“…In more detail, a strongly dissociative potential energy curve of a light molecule may lead to dissociation before the Auger decay and to high kinetic energies of the atomic fragments. If the geometry of the experiments allows selecting one particular direction of fragmentation, then the velocity of these core-excited fragments is either added to or subtracted from the velocity of the emitted resonant Auger electron, resulting in splitting of the Auger lines [23][24][25] . Such an observation is therefore restricted to ultrafast dissociation of molecules and is not related to the effect we have seen.…”
Section: Resultsmentioning
confidence: 99%
“…Triggered by these studies, Ueda et al [49] studied the resonant Auger decay of F1s → a * 1 excited, ultrafast dissociating CF 4 molecules, and found that the F1s −1 atomic-like Auger line is split into two Doppler-shifted components due to the emission of the Auger electrons by a fragment in motion, when the electron emission is detected along the polarization vector of the light. Since the Doppler shift is inherently connected to the photoabsorption process and the nuclear motion before the Auger decay takes place, and since ultrafast fragmentation is initiated on the core-excited state potential surface, the observation of the Doppler splitting constitutes a direct proof that in the case of CF 4 the asymmetric nuclear motion proceeds in the F1s-excited state, along the direction of the polarization vector of the incident light, leading to symmetry lowering from T d to C 3ν .…”
Section: Fig 14 Magnified 4σmentioning
confidence: 99%
“…Interestingly, in comparing the results for the asymptotic kinetic energy value for the F fragment, as obtained from the Born-Haber cycle type model of Wiesner et al [46], to the average kinetic energy of the F fragments, as estimated from the Doppler splitting, Ueda et al [49] found that in the case of ultrafast dissociating CF 4 , the fragments are not fully accelerated when the Auger decay takes place, which is in contrast to what has been seen for the HF/DF case. This finding suggests that the residual energy is kept in the fragment of CF 3 in the form of vibrational energy.…”
Section: Fig 14 Magnified 4σmentioning
confidence: 99%
“…The spectral line profiles in the electron energy spectra can also provide information on the ultrafast processes, such as the competition between the electronic decay and the nuclear motion. [13][14][15][16][17][18] Information on the interferences and phase shifts of the partial waves that describe the photoionization process itself 19 can also be retrieved by measuring the angular distribution of the ejected electrons with respect to the light polarization axis or to the propagation direction of the photon beam. 20 The combination of electrons and ions spectrometers in a sophisticated coincidence technique constitutes a powerful way to provide a direct view on a molecular reaction process by correlating all physical parameters of the emitted eleca) Electronic mail: liu@synchrotron-soleil.fr.…”
Section: Introductionmentioning
confidence: 99%